Coordinated control of distributed generation system with improved generalised enhanced phase locked loop control algorithm. Issue 11 (27th November 2018) - Kewat, Seema; Singh, Bhim
Abstract : Here, a distributed generation system (DGS) is proposed that allows the different distributed energy resources to operate in coordination with others to provide the electricity in rural areas. Two individual controls are used in the DGS: (i) solar maximum power point tracking (MPPT) and the battery protection control, and (ii) voltage source converter (VSC) control. The proposed VSC control algorithm is based on an improved generalised filter algorithm for power quality improvement of the DGS. This control strategy effectively regulates the active power flow and provides the harmonics mitigation, reactive power compensation, and load balancing in the DGS with low steady‐state error and fast dynamic response under high impulsive noise with DC‐offset component. The solar MPPT control is designed on the basis of battery state of charge (SOC). In this control, the solar PV array operates in limited power point tracking (LPPT) after the storage battery surpasses the maximum SOC limit. In LPPT control, the solar PV MPPT operates in the voltage source operating region of PV array characteristic, thereby, reducing the power generation and avoids the overcharging of the storage battery. The proposed DGS performance is validated through test results under dynamics and steady‐state conditions.